Investigating the inclusiveness of the usipa value chain in Malawi - Muhonda, P.; Rice, E.; Bennett, A.; Liverpool-Tasie, Saweda Lenis Onipede; Belton, Ben; Abaidoo, E. (Elsevier, 2024)
Value chain research increasingly seeks to assess the inclusiveness of value chains to better understand how to promote equitable and pro-poor development. This trend is especially relevant for small-scale fisheries value chains, which provide livelihoods, food security, and a social safety net for rural poor in many countries. Despite recent efforts to assess value chain inclusiveness, substantial knowledge gaps persist in small-scale fisheries value chains with respect to distribution of and access to benefits within and across different value chain nodes, particularly in the midstream (e.g. traders and processors). This study addresses this important research gap by utilizing an access mapping approach concerned with the distribution of benefits along the value chain for usipa (Engraulicypris sardella) in Malawi. Using a mixed methods approach, this analysis utilizes quantitative survey data (n = 929) at various nodes of the usipa value chain (fishers, processors, wholesalers, retailers), as well as qualitative focus group data (n = 60) and key informant interviews (n = 6), all collected in 2019. In line with the Structure-Conduct-Performance Paradigm, this study identifies value chain actors’ roles (structure), analyzes processes (conduct), and assesses the distribution of and access to income and in-kind benefits for different actors both within and across value chain nodes (performance). We calculate net income (revenues – expenses) for individual actors in each node of the value chain and find that (a) access to and distribution of income benefits from usipa vary substantially at group and individual levels; and (b) actors’ net income from the usipa value chain is negatively affected by unequal power distribution, price volatility and trade institutions, inadequate market infrastructure, social relations, and gender dynamics. This study advances approaches to study value chain inclusiveness, emphasizing the need to attend to variation and drivers acting at multiple scales, ranging from whole value chain structure to individual traders.